Model Pemberdayaan Dan Evaluasi Progam Penyedian Air Minum Berbasis Masyarakat (PAMSIMAS) Studi Kasus Pada Badan Pengelola Sarana Pengadaan Air Minum dan Sanitasi (BP-SPAMS) Andanawarih Desa Sudimara Kecamatan Cilongok Kabupaten Banyumas - Gentur Jalunggono; Rian Destiningsih (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
Pamsimas is a government program of the provision of clean water and sanitation that is administered by the community in the village level. Pamsimas takes a significant amount of funds and it is very beneficial for the people so that itssustainability is highly important. Sudimara were in high shortage of clean water. Therefore, in 2011 Sudimara villages received pamsimas. Based on the evaluation on such aspects as access to clean water, availability of sanitation, community empowerment, the improvement in healthy lifestyle by washing hands before meals and defecation in a privy and the availability of sanitation